Revisão taxonômica de Dissomphalus Ashmead 1893 (Hymenoptera, Bethylidae) no Espírito Santo, Brasil. - Colombo, Wesley Dondoni (2017)
Forty-two species of Dissomphalus Ashmead, 1893 are reviewed, 21 of them are described and illustrated: Dissomphalus botocudus sp. nov., D. fredi sp. nov., D. tupinikim sp. nov., D. guarani sp. nov., D. congo sp. nov., D. rosangelae sp. nov., D. waedeagus sp. nov., D. amana sp. nov., D. potyra sp. nov., D. pyata sp. nov., D. clovisi sp. nov., D. kuara sp. nov., D. miriamae sp. nov., D. cacirus sp. nov., D. mirim sp. nov., D. secretus sp. nov., D. caparao sp. nov., D. capixaba sp. nov., D. ibirapitanga sp. nov., D. purius sp. nov. and D. taiabocu sp. nov. Six species are registered for the first time from Espírito Santo: D. brasiliensis Kieffer, D. bahiensis Redighieri & Azevedo, D. dumosus Evans, D. incomptus Evans, D. refertus Alencar & Azevedo and D. umbilicus Azevedo. Three species were reidentified: D. napo Evans, D. truncatus Azevedo and D. vallensis Azevedo. Among fifteen species-groups which recognized in the genus in Espírito Santo, amana species-group; amplus species-group and secretus species-group are newly proposed.